Association Between Gastroesophageal Flap Valve and Endoscopically Diagnosed Gastroesophageal Reflux Disease According to Lyon Consensus: A Meta-analysis of Asian Studies. Issue 5 (11th May 2022) - Bao, Yun; Chen, Xiaosu; Xu, Ying; Wang, Yan; Lin, Lin; Tang, Yurong
Abstract : Background: Lyon Consensus altered the previous understanding of endoscopic gastroesophageal reflux disease (GERD) and pointed out that only high-grade reflux esophagitis (RE) [Los Angeles (LA) grades C or D], Barrett's esophagus or peptic stricturing were considered confirmatory evidence for GERD but low-grade RE (LA grades A or B) was regarded as suspected GERD. We aimed to summarize the possible relationship between gastroesophageal flap valve (GEFV) and endoscopic GERD according to Lyon Consensus using meta-analysis of studies done in Asia. Materials and Methods: Comprehensive searches of PubMed, WOS, Embase, SinoMed, and CNKI databases were completed to identify eligible studies published before September 22, 2019. A total of 237 articles have been reviewed and 2 reviewers independently evaluated the eligibility for inclusion, extracted, and analyzed the statistical data. The pooled risk ratios (RRs) with 95% confidence intervals (CI) were measured for the association. Random-effects models were used when observing significant heterogeneity. Results: A total of 15 studies were included and we found that abnormal GEFV (III and IV) could be associated with RE and the correlation become stronger as the grade increases (RE-A vs. controls—RR: 2.186, 95% CI: 1.560-3.064, P <0.001; RE-B vs. RE-A—RR: 1.268, 95% CI: 1.128-1.425, P <0.001; RE-C vs. RE-B—RR: 1.181, 95% CI: 1.000-1.395, P =0.049; RE-D vs. RE-C—RR: 1.471, 95% CI: 1.151-1.879, P =0.002). Both suspected GERD (RR: 2.400, 95% CI: 1.761-3.271, P <0.001) and endoscopic GERD (RR: 1.388, 95% CI: 1.127-1.711, P =0.002) were related to abnormal GEFV. Conclusion: Abnormal GEFV could provide useful information for reflux conditions, but it could not distinguish confirmatory GERD from low-grade RE under the upper endoscopy.